Pillars of Social Policy for Higher Education in the UAE - Darwish, Fatima; Al-Othman, Hussein (Al-Adab Journal, 2025)
This study aims to identify the pillars of the social policy of higher education in the United Arab Emirates. To achieve this goal, the study adopted the qualitative approach that is based on the collection of information and documents, for the phenomenon to be studied, which is to identify the basic pillars from which the social policy of higher education in the country is derived and on which it is based. The qualitative approach employed Using descriptive analysis, which requires This requires collecting data from secondary sources It included the content of the the State Constitution, laws and legislation, decrees and decisions of official institutions in making social policy for higher education. In addition, the study collecting data from references, letters, official reports, charters, and global and local agreements. This method aimed at making an objective description. The results showed that the pillars of the social policy of higher education in the UAE are based on a fixed and well-known set of pillars. These pillars constitute the basic foundations on which the policy is based and from which the legal framework for this policy is determined. These pillars are: Laws, legislations, decisions, and current and future decrees issued by official institutions in making social policy for higher education, represented in the legislative authority, the executive authority, and the judiciary in the state. The policy is based on Divine laws, the Constitution, global and local charters and treaties, the ideology of the state, and cultural heritage. These sources crystallize the foundations of the philosophy of higher education.